Analisis Status Gizi Siswa SD Bustanul Ulum Batu Busuk Padang Melalui Pengabdian Masyarakat Berbasis Pengukuran Indeks Massa Tubuh - Dwi yulia; Rikarni Rikarni; Ellyza Nasrul; Husni Husni; Elfira Yusri; Zelly Dia Rofinda; Efrida Efrida; Syofiati Syofiati; Yhosie Anto Chicamy; Deswita Sari; Desywar Desywar; Dian Pertiwi; Almurdi Almurdi; Rismawati Yaswir; Atika Indah Sari; Nanda Oktavia (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Nutritional status is an important indicator that determines the quality of health and development of school-age children. Adequate nutrition supports children's physical growth and cognitive abilities, and contributes to academic achievement. This community service activity aims to analyze the nutritional status of Bustanul Ulum Elementary School students by measuring height, weight, and Body Mass Index (BMI). The method used is quantitative descriptive with a sample of 150 students from grades 1 to 6. Measurements were carried out using standard and calibrated measuring instruments, while BMI was calculated using the formula body weight (kg) divided by the square of height (m²). The results showed that 75% of students had normal nutritional status, 10% were underweight and stunted, and 15% were overweight and obese. Factors that influence nutritional status include an unbalanced diet, lack of physical activity, and family socio-economic background. Children from families who have access to healthy food and good nutrition education tend to have better nutritional status. Based on these results, a comprehensive intervention program is needed in the form of nutrition education for students and parents, provision of healthy food at school, and promotion of regular physical activity. Collaboration between schools, health workers, and parents is essential to create an environment that supports optimal and sustainable child growth and development.